1910 Ga. Laws 134 - (:unkn) unknown (My University, 1910)
§ 2: Prohibited minors under the age of 18 from obtaining a license to carry. Also required license applicant to pay one hundred dollar bond.
Keywords: POSSESSION - MINORS